Suplementação de potássio e cálcio contribui na proteção osmótica e iônica em Jatropha curcas L. exposta à salinidade - Melo, Yuri Lima (Universidade Federal Rural do Semi-Árido, 2016)
The supplying of 9 mM K+ and 6 mM Ca2+ in the composition of three salt treatments (control; 75 and 150 mM NaCl) were evaluated in leaves, stem and roots of Jatropha curcas plants for 24 and 240 hours of exposure, based on growth indicators, water status, membranes integrity and ion stress and osmotic adjustment indicators. Salt reduced plant growth in all treatments regardless of time of exposure. The water status after 24 h was kept in leaves (75 mM) and roots (150 mM) and in all plant parts after 240 h regardless of the addition K+ or Ca2+. There were no membrane damage in 75 and 150 mM treatments in leaves and stem after 24 h. The sodium levels increased regardless of the plant part and treatment, however both K+ and Ca2+ levels were higher than Na+, helping in the ion toxicity mitigation (K+/Na+; Ca2+/Na+) in almost all the plant parts, regardless of exposure time. The highest values of K+/Na+ and Ca2+/Na+ ratios were observed in salt treatments supplied with K+ and Ca2+, respectively. It was observed in leaves (Sal1) and roots (Sal2), 24 h after treatment (DT), that the maintenance of water status (CRA) suggests an osmotic adjustment partially assigned to the increase of total soluble proteins (PST) and proline (PRO) levels and also to the membrane integrity maintenance in leaves and amino acids (AALT), total soluble sugars (AST) and starch levels maintenance in J. curcas roots. Increases in NaCl concentrations lowered the CRA in J. curcas stems, however the membrane integrity maintenance of this part seems to be associated to the increases of AALT, PRO and AST levels. In leaves, the addition of K+ to the salt solution increased PST and starch levels in Sal1 + K+ and AALT in Sal2 + K+ 24 h after treatment. In roots, the addition of K+ increased the PST, ALLT and PRO levels in Sal1+K+ treatment, as well as the AST levels in treatment Sal2 + K+, 24 h after treatment. The addition of K+ to the salt solution promoted an increase in PST, PRO and AST levels in Sal1 + K+ treatment in stem 24 h after treatment. The maintenance of CRA happened in all plant parts, 240 h after treatment and regardless of the NaCl concentration in most of the plant parts evaluated may be related to the maintenance in the PST, AALT and PRO levels. For all plant parts, the relation between carbohydrates and osmotic adjustment in J. curcas 240 h after treatment is not clear. The addition of K+ to the salt solution increased AALT (Sal1 + K+), PRO, AST (Sal2 + K+) and starch (Sal1 + K+) levels in leaves; PST, AALT (Sal1 + K+) and AST (Sal2 + K+) levels in stem; and AALT, PRO and starch levels only in the Sal1+K+ treatment. For all the plant parts and when exposed to the Sal1 + Ca2+ treatment 24 h after treatment, the supplying with Ca2+ increased the PST levels. In the same period, the supplying with Ca2+ increased the AALT levels mainly in leaves. After 240 h exposure, the presence of Ca2+ increased the AALT levels in all plant parts exposed to the Sal1 + Ca2+ treatment. PRO levels were increased with the supplying of Ca2+ mainly in leaves, 240 h after treatment. Stem of J. curcas was the part that had the highest increase of AST levels after the addition of Ca2+ to the salt solution in both times of exposure. Increases of starch levels were observed mainly in leaves in both exposure times. In conclusion, both K+ and Ca2+ individual additions to the salt solution supported the maintenance of ionic homeostasis and contributed to the increase of K+/Na+ and Ca2+/Na+ ratios, alleviating the toxicity effects by sodium in most of the evaluated plant parts, regardless of the exposure time and dosage of NaCl tested. Additionally, the osmotic adjustment observed in J. curcas occurred mainly by nitrogen compounds, being both K+ and Ca2+ individual additions related to the increases of most of the compatible solutes studied. The contribution of K+ and Ca2+ supplying in osmotic adjustment verified in J. curcas showed distinct responses in terms of exposure time, NaCl dosage and plant organ
Potassium and calcium supplementation contributes to osmotic and ionic protection in Jatropha curcas L. exposed to salinity
Keywords: Pinhão-manso; Estresse iônico; Ajustamento osmótico; Estresse salino; Potássio; Cálcio; Physic nut; Ionic toxicity; Osmotic adjustment; Salt stress; Potassium; Calcium; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA